1995
DOI: 10.1111/j.1532-5415.1995.tb05808.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Capacity to Comply with Medication Regimens in Older Patients

Abstract: A significant number of medically ill outpatients encountered difficulty in understanding or remembering correctly hypothetical but realistic medication regimens. This suggests that an older medical patient's cognitive and functional capacity to comply with medication regimens of differing complexity can be specifically assessed before the start of the regimen and probably should be assessed in patients whose compliance capacity is in question. The assessment instrument under development in this study may be h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 20 publications
0
26
0
1
Order By: Relevance
“…; Edelberg, Shallenberger, & Wei, 1999;Fitten, Coleman, Siembieda, Yu, & Ganzell, 1995;Meyer & Schuna, 1989;Patterson et al, 2002;Raehl, Bond, Woods, Patry, & Sleeper, 2002;Ruscin & Semla, 1996), questionnaires (Bennett et al, 2001;de Klerk, van der Heijde, Landewe, van der Tempel, & van der Linden, 2003;Yamada, Sugiyama, Ashida, Ohwaki, & Fujii, 2001), home-based measures (Brown et al, 1998;Stewart, Pearson, Luke, & Horowitz, 1998;West et al, 1997), and pharmacy-type interventions (patient education, pharmacist-developed discharge plans; Ali, Laurin, Lariviere, Tremblay, & Cloutier, 2003;Al-Rashed, Wright, Roebuck, Sunter, & Chrystyn, 2002;Grant, Devita, Singer, & Meigs, 2003;Hoffman et al, 2003;Jensen, 2003;Lowe, Raynor, Purvis, Farrin, & Hudson, 2000;Nazareth et al, 2001;Sturgess, McElnay, Hughes, & Crealey, 2003). A majority of the measures are limited by either their use by clinic patients or with patients using a specific drug type, narrow coverage of compliance issues, little utility for use with an entire drug regimen, lack of validation testing, or testing outside the United States.…”
mentioning
confidence: 99%
“…; Edelberg, Shallenberger, & Wei, 1999;Fitten, Coleman, Siembieda, Yu, & Ganzell, 1995;Meyer & Schuna, 1989;Patterson et al, 2002;Raehl, Bond, Woods, Patry, & Sleeper, 2002;Ruscin & Semla, 1996), questionnaires (Bennett et al, 2001;de Klerk, van der Heijde, Landewe, van der Tempel, & van der Linden, 2003;Yamada, Sugiyama, Ashida, Ohwaki, & Fujii, 2001), home-based measures (Brown et al, 1998;Stewart, Pearson, Luke, & Horowitz, 1998;West et al, 1997), and pharmacy-type interventions (patient education, pharmacist-developed discharge plans; Ali, Laurin, Lariviere, Tremblay, & Cloutier, 2003;Al-Rashed, Wright, Roebuck, Sunter, & Chrystyn, 2002;Grant, Devita, Singer, & Meigs, 2003;Hoffman et al, 2003;Jensen, 2003;Lowe, Raynor, Purvis, Farrin, & Hudson, 2000;Nazareth et al, 2001;Sturgess, McElnay, Hughes, & Crealey, 2003). A majority of the measures are limited by either their use by clinic patients or with patients using a specific drug type, narrow coverage of compliance issues, little utility for use with an entire drug regimen, lack of validation testing, or testing outside the United States.…”
mentioning
confidence: 99%
“…Les recherches sur l'observance mettent l'accent presque toujours sur les difficultés que les aînés rencontrent dans la prise des médicaments tels que prescrits ainsi que d'autres facteurs liés aux attitudes et comportements des aînés. Les recherches indiquent que les facteurs suivants sont associés à un taux d'observance moindre : -difficultés à lire et à comprendre l'étiquette des médicaments (Fitten et al, 1995 ;Morrell et al, 1990) -difficultés avec les emballages (Kottke et al, 1990) -grand nombre de médicaments consommés ou de prises quotidiennes (Botelho et Dudrak, 1992 ;Spagnoli et al, 1989) -être dépressif (Carney et al, 1995) -troubles de la mémoire (Nananda et al, 1990) -effets secondaires déplaisants ou peur des effets secondaires de la part des aînés (Nananda et al, 1990 ;Spagnoli et al, 1989) -jugement par les aînés que la médication n'est pas nécessaire (Nananda et al, 1990) -mauvaise compréhension du schéma de traitement (Spagnoli et al, 1989) -disparition des symptômes (Spagnoli, 1989) …”
Section: L'observance Et Les Réactions Indésirables Aux Médicaments (unclassified
“…A six month randomised controlled trial of a PDVS demonstrated positive trends in clinical outcomes and cost reduction [5]. Furthermore, poor adherence to medication regimens has been found to be a causative factor of repeated unplanned hospital readmissions [6]; research has shown that pharmacist domiciliary visits can encourage an improvement in patient adherence [7,8].…”
Section: Introductionmentioning
confidence: 99%